Study on Resource Recovery of Noncombustible/Bulky Waste before and after Electric Appliances Recycling Act - Imai, Tsuyoshi; Li, Boyang; Higuchi, Takaya; Ukita, Masao; Sekine, Masahiko (Journal of the Japan Society of Waste Management Experts, 2008)
In order to improve resource recovery and treatment systems for municipal solid waste, a detailed investigation was conducted on noncombustible/bulky waste treatment processes both pre- and post- enactment of the electric appliances recycling act. A composition analysis of shredded noncombustible/bulky waste (12 times; 60 samples in total) was carried out by manual selection in order to estimate the material balance. It was understood from this that resource recovery of electric appliances has largely been improved, with the recovery of glass and plastics, etc. being the main factor. Moreover, about one-eighth of the noncombustible materials found in the incinerator (i.e. batteries) originated from noncombustible/bulky wastes. In addition to improving noncombustible/bulky waste treatment systems, it is also necessary to develop strategies for reducing the amount of noncombustible materials being mixed into combustible waste systems.